Kalervo Palsa : Toinen tuleminen. - Heinimäki, Jaakko; Hänninen, Ville; Karjalainen, Tuula; Liksom, Rosa; Pallasmaa, Ullamaria; Paloposki, Hanna-Leena; Robbins, Nina (Helsinki : KIASMA Museum of Contemporary Art, 2002)
A master of black irony, Kalervo Palsa revealed in his work the dismal side of life. In his art, he delved into ghe darkest abysses of the human mind : a world of sexuality mingling with death, of earthly mana and Arctid passion. The technically superb artist had a continuous need to shock and disturb his viewers, and it was precisely this aspect of his personality that laid the foundation for Palsa's madly idiosyncratic style.
bibliog. p. 180-185
expografie p. 186-189
Engels
Fins
Kalervo Palsa : Toinen tuleminen / Resurrection, KIASMA (Museum of Contemporary Art) Helsinki, 14.9.2002-5.1.2003
boek
Keywords: Palsa, Kalervo